2014
DOI: 10.1007/s10865-014-9561-x
|View full text |Cite
|
Sign up to set email alerts
|

Spousal social support and strain: impacts on health in older couples

Abstract: Using a nationally representative sample of couples aged 51+ in the United States (N = 1,923 couples), the current study investigated whether both partners’ perceptions of relationship support and strain are associated with an individual's self-rated health and functional limitations. The sample had an average age of 67.17 years (SD = 9.0; range 50–97). Actor–Partner Interdependence Models adjusting for couple interdependencies were applied using multilevel models. After accounting for age, education, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Not all studies have found the health-related effects of negative exchanges to outweigh those of positive exchanges (e.g, Ryan, Wan, & Smith, 2014; Walen & Lachman, 2000). On balance, though, the preponderance of evidence suggests that the health-related effects of negative social exchanges are at least as potent, and often more potent, than the effects of positive social exchanges (Rook, 1998).…”
Section: Evidence Linking Positive and Negative Social Exchanges To Hmentioning
confidence: 99%
“…Not all studies have found the health-related effects of negative exchanges to outweigh those of positive exchanges (e.g, Ryan, Wan, & Smith, 2014; Walen & Lachman, 2000). On balance, though, the preponderance of evidence suggests that the health-related effects of negative social exchanges are at least as potent, and often more potent, than the effects of positive social exchanges (Rook, 1998).…”
Section: Evidence Linking Positive and Negative Social Exchanges To Hmentioning
confidence: 99%
“…Married couples are not only influenced by the external stresses experienced in their lives but stresses that are internal to the marriage. Negative aspects of the marital relationship (e.g., negative or hostile behaviors; overall strain) are linked with increased cardiovascular activity (Kiecolt-Glaser & Newton, 2001;Robles & Kiecolt-Glaser, 2003), poorer self-rated health, and greater functional limitations (Ryan, Wan, & Smith, 2014). In a meta-analysis assessing the relationship between marital quality and health, Robles, Slatcher, Trombello, and McGinn (2013) found that marital dissatisfaction was consistently related to structural indicators of cardiovascular disease as well as functional indicators, including blood pressure.…”
Section: Negative Relationship Quality and Blood Pressure Among Marrimentioning
confidence: 99%
“…The relationship between the patient and their partner is one of the most obvious and important sources for social support and help‐seeking advice. Spousal social support has been shown to be an important determinant of the patient's well‐being (Ryan, Wan, & Smith, ). However, the input from partners, relatives and significant others is not always helpful or supportive, and negative social interactions can have negative implications for well‐being and health and may also have an impact on help‐seeking behaviour.…”
Section: Introductionmentioning
confidence: 99%